Analysis of “national security” problems and mechanisms for adoption “political solution” using the example of the Kyrgyz Republic (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article is devoted to the study of the analysis of theoretical aspects of national security and technologies for making political decisions. Analysis of political tasks and technology of interaction between the state and the Jogorku Kenesh of the Kyrgyz Republic, which made it possible, through the prism of manipulative, normative, structural-functional, and comparative approaches, to present models using the example of the Jogorku Kenesh as a multidimensional socio-political phenomenon, as well as an integrated interdisciplinary system of knowledge
Keywords: Jogorku Kenesh of the Kyrgyz Republic, national security of the Kyrgyz Republic, political management, public administration, national interests, national priorities, information analysis, interaction between the state and the Jogorku Kenesh, security threats, strategy for ensuring national security, concept of national security